Etiology, clinical characteristics and mortality among Indian patients with Addison’s disease - Gunna, Sriharsha; Singh, Mahaveer; Pandey, Rakesh; Marak, Rungmei S K; Aggarwal, Amita; Mohanta, Bibhuti; Yu, Liping; Bhatia, Eesh (Endocrine Connections, 2023)
The etiology, presentation and mortality of patients with primary adrenal insufficiency (PAI) in developing countries may differ from economically developed nations. However, information in this regard is scanty. The aim of this study was to determine the etiology and compare the clinical characteristics and mortality in infectious and autoimmune causes of PAI in Indian patients. All eligible (n = 89) patients (ages 15–83 years) diagnosed with PAI between 2006 and 2019 were studied. Patients were followed for a median duration of 5.9 (range 0.1–15.7) years. Eighty-six subjects underwent an abdominal computerized tomography scan or ultrasonography, and adrenal biopsy was performed in 60 patients. The most frequent etiologies of PAI were adrenal histoplasmosis (AH, 45%), adrenal tuberculosis (AT, 15%), autoimmunity (AI, 25%) and primary lymphoma (6%). Forty-two percent of patients presented with an acute adrenal crisis. AH and AT could not be differentiated on the basis of clinical features, except for a greater frequency of hepatomegaly–splenomegaly and type 2 diabetes mellitus (63% vs 15%, P < 0.01) in the former. Patients with an autoimmune etiology had a higher frequency of 21-hydroxylase antibodies (41% vs 3%) and autoimmune thyroid disease (46% vs 5%) vs those with infectious etiologies. Mortality was significantly higher in AH (45%) compared with AT (8%) or AI (5%) (P = 0.001). Causes of death included adrenal crises, progressive AH and unexplained acute events occurring at home. In conclusion, infections, especially AH, were the most frequent cause of PAI in north India. Despite appropriate therapy, AH had very high mortality as compared with AT and AI.